On the measurement of wall shear stress with a patch-type micro-fabricated hot-film sensor - Takuya SAWADA; Osamu TERASHIMA; Yasuhiko SAKAI; Kouji NAGATA; Mitsuhiro SHIKIDA; Yasumasa ITO; Sora MURAMATSU (Journal of Fluid Science and Technology, 2014)
In this study, a new patch-type hot-film sensor is devised to measure wall shear stress, and its measurement accuracy is validated. The sensor consists of heaters on a thin polyimide film and a flexible printed circuit. The film is supported by silicone rubber with a hole in it, which forms a cavity under the heating element to improve the response of the sensor. Static and dynamic response tests show that the sensor properly responds to the wall shear stress and that its roll-off frequency is 10 Hz. Results also show that the sensor can measure the time-averaged wall shear stress in a boundary layer of the wall jet and can detect wall shear stress caused by the velocity gradient of the cross-streamwise profile of streamwise velocity in a boundary layer.